2007
DOI: 10.1063/1.2746846
|View full text |Cite
|
Sign up to set email alerts
|

Using redundant coordinates to represent potential energy surfaces with lower-dimensional functions

Abstract: We propose a method for fitting potential energy surfaces with a sum of component functions of lower dimensionality. This form facilitates quantum dynamics calculations. We show that it is possible to reduce the dimensionality of the component functions by introducing new and redundant coordinates obtained with linear transformations. The transformations are obtained from a neural network. Different coordinates are used for different component functions and the new coordinates are determined as the potential i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
101
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 96 publications
0
101
0
Order By: Relevance
“…(6) and (7) grows combinatorially with d and k. For example, even if k 5 4 is enough, there are 220 component functions for a sixatom molecule. We have shown [25] that it is possible to reduce substantially the number of terms using an expression similar to Eq. (7) in transformed coordinates.…”
Section: Transformed Coordinates and Dimensionality Reductionmentioning
confidence: 99%
See 4 more Smart Citations
“…(6) and (7) grows combinatorially with d and k. For example, even if k 5 4 is enough, there are 220 component functions for a sixatom molecule. We have shown [25] that it is possible to reduce substantially the number of terms using an expression similar to Eq. (7) in transformed coordinates.…”
Section: Transformed Coordinates and Dimensionality Reductionmentioning
confidence: 99%
“…Finding the coordinates q can be thought of as adding a layer, with linear neurons, to a classic NN. [25,28] When L k > 1, usually the total number of new coordinates kL k > d, which is why the method was called Redundant Coordinate HMDR neural network (RC-HDMR-NN). [25] We have shown that this approach does result in a substantially smaller number of terms and/or required k compared to RS-HDMR [Eqs.…”
Section: Transformed Coordinates and Dimensionality Reductionmentioning
confidence: 99%
See 3 more Smart Citations